Best Answer

divide by 2 to give 3.5x = y

That is all you can do without further information about x.

Q: 7x equals 2y solve for y?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2y + 7x + y-1?

This equation is unsolvable without knowing one of the values of either x or y.

For y - 2y - 3y equals 0, y equals 0.

Double first equation: 10x + 2y = 10Subtract second equation: 7x = 7x = 1, y = 0

are those two different problems ? ... i am going to solve them as if they are 14x-2y=78 (re arange the terms to be easily solved) -2y=78-14x (times by -1) 2y= -78+14x (divide all terms by 2) y=-39+7x (so) y=7x-39 2x-2y=6 (re arange the terms to be easily solved) -2y=6-2x (times by -1) 2y=2x-6 (divide all terms by 2) y=x-6

Related questions

2y + 7x + y-1?

7x-2y = 14 -2y = -7x+14 y = 3.5x-7

Manipulate such that y is the subject of the equation 7x - 2y = -14 2y = 7x +14 y = (7/2)x + 7

This equation is unsolvable without knowing one of the values of either x or y.

For y - 2y - 3y equals 0, y equals 0.

7x + y = 4y = 4 - 7x

-2y = 10 2y = -10 y = -5

7x-2y=10 -2y=10-7x y=-5+(7/2)x y=(7/2)x-5 (Final answer)

Double first equation: 10x + 2y = 10Subtract second equation: 7x = 7x = 1, y = 0

are those two different problems ? ... i am going to solve them as if they are 14x-2y=78 (re arange the terms to be easily solved) -2y=78-14x (times by -1) 2y= -78+14x (divide all terms by 2) y=-39+7x (so) y=7x-39 2x-2y=6 (re arange the terms to be easily solved) -2y=6-2x (times by -1) 2y=2x-6 (divide all terms by 2) y=x-6

2y = 4 (divide both sides by 2 to solve) y = 2

7x + y = 8 Subtract 7x from each side of the equation: y = -7x + 8